The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1084/jem.181.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to desmoplakin I and II in patients with erythema multiforme.

Abstract: Sllll'RiillaryErythema multfforme (EM) represents a syndrome of chronic recurrent inflammatory skin disease. Depending on the severity and extent of skin and mucosal involvement, it is defined either as EM minor or EM major. In this study we demonstrate the presence of autoantibodies (aAbs) against desmoplakin I and II, two major proteins of the desmosomal plaque, in six of six patients with the severe variant of EM, EM major. Light microscopic studies of lesional skin and mucous membranes localized in vivo bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 39 publications
(50 reference statements)
2
50
0
Order By: Relevance
“…A small number of patients with recurrent erythema multiforme major have antibodies against desmoplakins and will therefore have a positive indirect IF on bladder epithelium. These cases are distinguished from PNP in several ways: (1) they do not have an underlying malignancy; (2) they do not have antibodies against the plakin proteins that are more speci¢c for PNP, that is, envoplakin and periplakin; and (3) the antibodies are transient and are only detecable during episodes of active disease (Foedinger et al, 1995). The autoantibodies in PNP are constantly present.…”
Section: Diagnosismentioning
confidence: 97%
“…A small number of patients with recurrent erythema multiforme major have antibodies against desmoplakins and will therefore have a positive indirect IF on bladder epithelium. These cases are distinguished from PNP in several ways: (1) they do not have an underlying malignancy; (2) they do not have antibodies against the plakin proteins that are more speci¢c for PNP, that is, envoplakin and periplakin; and (3) the antibodies are transient and are only detecable during episodes of active disease (Foedinger et al, 1995). The autoantibodies in PNP are constantly present.…”
Section: Diagnosismentioning
confidence: 97%
“…One reason for the different outcome of our study compared with the initial work (Foedinger et al, 1995(Foedinger et al, , 1996 might be the tight window between diagnosis of the disease and serum sampling in our cohort. This may have reduced the detection of epiphenoma following the preceding tissue destruction due to an extended inflammatory response (Cozzani et al, 2011).…”
mentioning
confidence: 79%
“…Infiltrating TO THE EDITOR Erythema exsudativum multiforme majus (EEMM) is a rare condition affecting both skin and mucous membranes. It is assumed that humoral immune reponses may contribute to the pathogenesis of the disease, and the presence of autoantibodies was described in 7 of 10 EEMM patients (Foedinger et al, 1995(Foedinger et al, , 1996. These autoantibodies were associated with desmosomal staining by direct immunofluorescence microscopy of skin and by indirect immunofluorescence tests using monkey esophagus as a substrate, and they produced 210/ 250 kDa bands by immunoblotting of epidermal extracts, and immunoprecipitated proteins of apparently 210/250 kDa from lysates of human keratinocytes.…”
mentioning
confidence: 96%
“…In fact, several reports demonstrate penetration of IgG autoantibody into living cells (19,20). Notably in keratinocytes, by using passive transfer and in vitro cell culture systems, a series of recent investigations have also demonstrated that IgG autoantibodies to desmoplakin I/II, entirely intracellular desmosomal antigens, can get into living cells and reach the target antigens (21)(22)(23). Moreover, anti-nuclear IgG antibodies from patients with systemic lupus erythematosus have been shown to penetrate into living epithelial cells via receptor-mediated endocytosis and subsequently localize to the corresponding intracellular target antigens (24).…”
Section: Discussionmentioning
confidence: 99%